XVI-wieczny dyskurs polemiczny w świetle pism Grzegorza Pawła z Brzezin - Hawrysz, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The subject of the analysis in the article are two editions of Grzegorz Pawełs of Brzeziny’s works treated as an update of the 16th-century polemical discourse. The purpose of the sketch is a preliminary description of this discourse, taking into account its parameters such as the institutional framework, cultural and social conditions, speakers and their interrelationships, the subject of speech, knowledge, basic concepts, ideas and values contained in the discourse.